Low dose colestipol in adolescents with familial hypercholesterolaemia. Issue 2 (February 1996) - Tonstad, S; Sivertsen, M; Aksnes, L; Ose, L
Abstract : The effects of orange flavoured colestipol granules, 10 g/day, in 37 boys and 29 girls aged 10-16 years with familial hypercholesterolaemia were examined first in an eight week double blind, placebo controlled protocol, then in open treatment for 44-52 weeks. All patients were on a low fat diet. Low density lipoprotein cholesterol levels were reduced by 19.5% by colestipol v 1.0% by placebo. Levels of serum folate, vitamin E, and carotenoids were reduced in the colestipol group, but not the vitamin E/cholesterol and carotenoid/cholesterol ratios or serum concentrations of vitamins A and D. After one year of colestipol, two thirds of the participants remained in the study, of whom half took > or = 80% of the prescribed dose. Those who took > or = 80% of the dose had a greater decrease in serum 25-hydroxyvitamin D levels than those who took < 80%. No adverse effects on weight gain or linear growth velocity were observed. Although low dose colestipol effectively reduces low density lipoprotein cholesterol levels, only a minority of adolescents adhered to the new formulation for one year. Folate and possibly vitamin D supplementation is recommended.